RECTANGULAR OPEN CHANNELS OF COMBINED ROUGHNESS - Retsinis, E.; Bobotas, S.; Demetriou, J. (European Scientific Journal, ESJ, 2013)
In this experimental study the Manning roughness coefficient n is examined, through a considerable number of laboratory measurements with artificially roughened walls of a rectangular open channel-which always has a smooth bed. The roughness elements are vertical rubber strips, which are systematically varying as far as theirs projections into the flowing water and theirs distances among them are concerned. The case of the completely smooth rectangular channel is also examined. Since n has the disadvantage of being in the metric system of units, some suitable dimensionless groups of parameters are used. n appears not to be constant at any present roughness condition and this probably is due to the nature of any flow, where even at the same Run its behavior is not constant. Apart from this, n is also varying in the completely smooth channel case. The results are strictly holding for uniform-subcritical-turbulent-steady water flows in rectilinear rectangular open channels of small longitudinal slope.